Предмет: Алгебра, автор: zzixx

упростить выражение x(x-1) (x-1) -(x-2) (x^2+2x+4)​

Ответы

Автор ответа: Sanya2263
0

х(х-1)(х-1)-(x-2)(x²+2x+4)​ = х(х²-2х+1)-(х³-2³) =

х³-2х²+х-х³+8 = -2х²+х+8.

Автор ответа: sadykovanatalya2004
0

Ответ:

x(x-1)(x-1) -(x-2) (x^2+2x+4)​=x(x-1)²-(x³-2³)=x(x²-2x+1)-x³+8=

=x³-2x²+x-x³+8=-2x²+x+8=2(4-x²)+x=2(2-x)(2+x)+x

Объяснение:

(a-b)²=a²-2ab+b²

a³-b³=(a-b)(a²+ab+b²)

a²-b²=(a-b)(a+b)

Похожие вопросы
Предмет: Русский язык, автор: МаРмЕлАд505
Предмет: Русский язык, автор: новенькая10